Rediscovery of a rare and endangered Apostolepis (Serpentes: Dipsadidae): reassessing species boundaries and phylogenetic relationships using integrative approaches - Entiauspe-Neto, Omar M.; Giraudo, Alejandro R.; Guedes, Thaís B. [UNESP]; Tiutenko, Arthur; Borges-Martins, Márcio; Koch, Claudia (My University, 2025)
Apostolepis is a diverse genus of small and fossorial dipsadid snakes, comprising 34 species ranging from Colombia southwards into Argentina. Most species are known from small series and very little is known regarding their phylogenetic relationships, morphological variation and diagnoses, which has caused a widespread historical taxonomic instability for the genus. Its southernmost representative, Apostolepis quirogai, is known solely from three specimens from the Mesopotamian and Uruguayan Savannas, with no new records in the last two decades. Its rarity, puzzling external morphology, and unique coloration pattern have significantly contributed to an uncertain systematic relationship for this species. We report the rediscovery of A. quirogai, providing an integrative species delimitation based on multivariate analyses, external morphology and molecular systematics, a redescription, an updated account of its morphological variation, geographic distribution, and a description of its cranial osteology. We provide a new phylogenetic hypothesis for the Elapomorphini, where we consistently recover A. quirogai nested within the Apostolepis assimilis species group, which is redefined and discussed here. We also provide a comparative osteological analysis of skull morphology for Apostolepis, providing insights into diagnostic characters and cranial evolution for the group.
Keywords: Elapomorphini; integrative taxonomy; morphology; Neotropics; osteology; Squamata